Nitrification control by adjusting pH in severely nitrified bulkwaters - Sarker, D.C.; Arumugam, Sathasivan (IWA Publishing, 2012)
Nitrification control is complicated and expensive, especially when nitrification has reached aseverely nitrifying stage. Under this condition, utilities usually apply re-chloramination with limitedsuccess. Adjusting pH may benefit utilities. However, it is not clear whether pH should be moved upor down, and pH adjustment will also alter the chloramine decay profile (biocide) and ammonia (food)concentration. It is important to understand how this behaviour will ultimately impact nitrifyingbacterial activity. We collected samples from severely nitrifying bulkwaters and adjusted the pHwithin a practical range to know which pH benefits the most. Results showed that even a slightincrease in pH can help in protecting the chloramine residual and suppressing nitrifying bacterialactivity.